2007
DOI: 10.1308/003588407x168235
|View full text |Cite
|
Sign up to set email alerts
|

The Differential Diagnosis of Foot Lumps: 101 Cases Treated Surgically in North Glasgow Over 4 Years

Abstract: INTRODUCTION There are a wide variety of different lesions which present as lumps of the foot. There have been very few studies which look at the presenting characteristics or the differential diagnosis of such lesions.PATIENTS AND METHODS All patients who underwent excision or biopsy of a foot lump over a period of 4 years were studied in order to determine patient demographics, presenting characteristics, diagnoses encountered and to assess the diagnostic accuracy of the surgeon. RESULTS In total, 101 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 4 publications
1
23
0
Order By: Relevance
“…The reason for this may well be that even though ganglion cysts are relatively frequent causes of foot lumps, their absolute incidence is rather low (Bakotic and Borkowski, 2001;Macdonald et al, 2007). In addition to this, ganglion cysts do not usually produce neurological symptoms (Brooks, 1952;Kliman and Freiberg, 1982;Harbaugh et al, 1997;Rozbruch et al, 1998;Pontious et al, 1999;Rawal et al, 2004;Macdonald et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reason for this may well be that even though ganglion cysts are relatively frequent causes of foot lumps, their absolute incidence is rather low (Bakotic and Borkowski, 2001;Macdonald et al, 2007). In addition to this, ganglion cysts do not usually produce neurological symptoms (Brooks, 1952;Kliman and Freiberg, 1982;Harbaugh et al, 1997;Rozbruch et al, 1998;Pontious et al, 1999;Rawal et al, 2004;Macdonald et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Ganglion cysts are more frequently located on the dorsum of the wrist, the palm of the hand, and the dorsolateral aspect of the foot. (Fleegler, 2006;Vatansever et al, 2006;MacDonald et al, 2007). It has been recently shown that ganglion cysts of the foot represent nearly 39% of lumps in that region (Macdonald et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, positive history of trauma, mass size, and even duration of symptoms is unreliable in discriminating neoplastic from nonneoplastic processes with regard to the distal extremities. 5,9 In some publications, preoperative clinical accuracy distinguishing benign or malignant neoplasms is less than 60%. 8,9 It must be remembered that more than 100 distinct histopathologic tumor types can arise from the skin, soft tissue, and bone in these locations.…”
Section: Specific Cytologic Diagnosis (No Of Cases) No (%) Of Casesmentioning
confidence: 99%
“…One reason for this may be the infrequency of malignancy in this location (<2% of all cases). [2][3][4][5][6][7][8][9][10] Previously, only 2 studies have specifically commented on the use of FNAB in the hand and wrist. 7,8 And, with the exception of scattered case reports or distal extremity cases reported within larger series, FNAB of the foot and ankle region has been largely neglected.…”
mentioning
confidence: 99%